2022
DOI: 10.5397/cise.2021.00738
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, Evaluation, and Management of Osteolysis After Total Shoulder Arthroplasty

Abstract: Radiographic osteolysis after total shoulder arthroplasty (TSA) remains a challenging clinical entity, as it may not initially manifest clinically apparent symptoms but can lead to clinically important complications, such as aseptic loosening. A thorough consideration of medical history and physical examination is essential to rule out other causes of symptomatic TSA—namely, periprosthetic joint infection—as symptoms often progress to vague pain or discomfort due to subtle component loosening. Once confirmed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Although DICOM tags are usually used to record imaging information, they can be subject to manual recording errors and may not include information that can be directly useful for other purposes. A number of different AI‐based classification algorithms have been created in recent years to recognize different important features of orthopaedic imaging data, such as imaging view, implant existence and implant type [21, 27, 41].…”
Section: Registry Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DICOM tags are usually used to record imaging information, they can be subject to manual recording errors and may not include information that can be directly useful for other purposes. A number of different AI‐based classification algorithms have been created in recent years to recognize different important features of orthopaedic imaging data, such as imaging view, implant existence and implant type [21, 27, 41].…”
Section: Registry Constructionmentioning
confidence: 99%
“…Recent studies have demonstrated that deep learning classification models can be trained to predict the manufacturer of surgical implants in postoperative radiographs. For example, a study created a deep learning model to identify 22 unique TSA implants from 8 manufacturers [21]. This model achieved a high accuracy of 97.1% with a high inference speed of 0.079 s per image.…”
Section: Registry Constructionmentioning
confidence: 99%
“…The mechanism of long-term aseptic artificial joint loosening includes biological factors, micromotion of the prosthesis, stress shielding, and individual genetic differences [ 7 ]. Among them, PPO induced by wear particles is the main cause of aseptic loosening of prostheses, which directly affects the service life of prostheses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Restoring physiological soft tissue tension provides stability and prevents complications such as aseptic loosening and osteolysis induced by stress shielding. 7,11,12 Overstuffing decreases the shoulder's range of motion and alters the lever arm, adding stress to the rotator cuff and potentially leading to the risk of secondary rotator cuff failure. 15,17 In advanced glenohumeral osteoarthritis, the humeral head is deformed because of loss of the humeral head height and the presence of peripheral osteophytes, making it difficult to preoperatively calculate the anatomically correct prosthetic humeral head size.…”
mentioning
confidence: 99%
“… 13 , 14 Restoring physiological soft tissue tension provides stability and prevents complications such as aseptic loosening and osteolysis induced by stress shielding. 7 , 11 , 12 Overstuffing decreases the shoulder’s range of motion and alters the lever arm, adding stress to the rotator cuff and potentially leading to the risk of secondary rotator cuff failure. 15 , 17 …”
mentioning
confidence: 99%